Comparing Individuals through the Speech Recognition Test Applied to Regional Live Voice and Recorded Speeches from Paraná State in Five Brazilian Counties - Mafra,Nicoli Valverde (2019)
Abstract Introduction Speech tests such as logoaudiometry measure the ability to perceive and recognize oral sounds. The Speech Recognition Index (SRI) is one of the speech tests adopted in clinical routine; it uses standardized live voice and recorded speeches. The live voice speech method can be influenced by intra and interspeaker variability, as well as by regionalism variability, whereas recorded tests show consistency in their presentation. Objective Analyzing results of the SRI test applied to live voiceand recorded speeches from Paraná State, in different Brazilian counties. Method The sample comprised 125 individuals, 25 fromeach county (Rio de Janeiro, Florianópolis, Porto Alegre, Salvador and Curitiba), from both sexes, in the age group 20 to 70 years; the SRI was applied in both techniques. Results The recorded speech method showed prevalence of hit improvement in Rio de Janeiro (40%), Salvador, Porto Alegre and Florianópolis (28%). Individuals from Salvador and Florianópolis subjected to the recorded speech method showed better results in the left ear. Individuals from Rio de Janeiro and Porto Alegre showed satisfactory results in both ears, whereas those from Curitiba did not show statistically significant difference between the left and the right ear. Conclusion The recorded CD application method showed prevalence of hit improvement (%) in the SRI responses in comparison to the live voice speech technique in most of the studied counties. According to the hit rate measured in the herein investigated counties, Rio de Janeiro showed the best results in the recorded speech method.